Diversity of Wild Mushrooms In Rupandehi District, Western Nepal - Aryal, Hari Prasad (Journal of Natural History Museum, 2018)
This paper highlights the one of the underappreciated natural resource of NTFPs, has high food and medicinal values. The area embraces different mycophagus ethnic communities. The work emphasized the knowledge on the use of various ways of the wild mushrooms in the different ethnic groups and communities in habiting in the district and to explore in the study area. This mycological investigation carried out in different area ranging between 90 and 1229 m asl in tropical deciduous riverine forest, to subtropical deciduous hill forest. The specimens are housed in the Central Department of Botany, Pathology Unit, Tribhuvan University. The collected samples represented 46 species of Basidiomycetes belongs to 32 genera, 20 families and 9 order. The mycoelements prevailing in this area need sustainable utilization and conservation. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 19-31